Hubungan Pola Makan Dan Tingkat Pengetahuan Dengan Kejadian Gastritis Pada Dewasa Awal Di Wilayah Puskesmas Warungkondang Kabupaten Cianjur Tahun 2022 - Faisal Firdaus; Sancka Stella G. Sihura; Bambang Suryadi (Lembaga Pengembangan Kinerja Dosen, 2023)
Gastritis is an acute and chronic inflammation of the gastric mucosa. Gastritis recurs with symptoms such as heartburn, nausea and vomiting. Gastritis occurs in people who have an irregular diet and eat foods that stimulate the production of stomach acid. In addition, gastritis can also occur due to lack of knowledge that alters to prevent the occurrence of gastritis. The purpose of this study was to determine the relationship between diet and level of knowledge with the incidence of gastritis in early adulthood in the Warungkondang Cianjur Health Center area. The type of research is quantitative with correlation research and using a cross sectional design, a sample of 76 respondents. The sampling technique is purposive sampling. It was found that the results of the analysis of the relationship between diet and the incidence of gastritis were as many as 48 (63.2%) respondents with poor diet with the incidence of gastritis who had gastritis. And for the level of knowledge with the incidence of gastritis there were as many as 40 (52.6%) respondents with a poor level of knowledge with the incidence of gastritis who had gastritis. The results of statistical tests of diet and level of knowledge obtained a value of pvalue = 0.000 smaller than 0.05. There is a relationship between diet and level of knowledge with the incidence of gastritis in early adulthood.